1989
DOI: 10.1523/jneurosci.09-06-02033.1989
|View full text |Cite
|
Sign up to set email alerts
|

Afferent basis of visual response properties in area MT of the macaque. I. Effects of striate cortex removal

Abstract: The middle temporal area (MT) of the macaque monkey is a region of extrastriate cortex involved in the analysis of visual motion. MT receives strong projections from striate cortex and from area V2, which is dependent on striate for visual responsiveness. Accordingly, the visual properties of MT neurons have been thought to reflect the further processing of its input from striate cortex. We examined the dependence of MT activity on pathways deriving from striate cortex by recording from MT neurons following re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
225
6
4

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(250 citation statements)
references
References 54 publications
15
225
6
4
Order By: Relevance
“…We found that neurons within the lesion projection zones of MT are strongly direction-selective, similar to those in normal marmoset MT. This result is in agreement with previous work in the macaque (Rodman et al, 1989;Girard et al, 1992). The fact that even neurons with displaced receptive fields show strong direction selectivity argues against the notion that this property is simply imposed on MT cells by afferents from hierarchically "lower" areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that neurons within the lesion projection zones of MT are strongly direction-selective, similar to those in normal marmoset MT. This result is in agreement with previous work in the macaque (Rodman et al, 1989;Girard et al, 1992). The fact that even neurons with displaced receptive fields show strong direction selectivity argues against the notion that this property is simply imposed on MT cells by afferents from hierarchically "lower" areas.…”
Section: Discussionsupporting
confidence: 92%
“…Lesions (Rodman et al, 1989) or brief inactivations (Bullier et al, 1994) of V1 in Old World monkeys do not completely abolish the visual responses of cells in some extrastriate areas, including the middle temporal area (MT), a result that is compatible with the above hypothesis. In contrast, a study in New World monkeys (Aotus trivirgatus) in which MT was studied immediately after a V1 lesion reported no residual activity in the sector of MT that corresponded, in visuotopic coordinates, to the destroyed part of V1 (Krubitzer and Kaas, 1992).…”
Section: Abstract: Marmoset; Vision; Extrastriate; Receptive Fields;mentioning
confidence: 54%
See 1 more Smart Citation
“…The same rank order applies to these stations in terms of processing because neuronal selectivity for orientation and the direction of movement is not present in the lateral geniculate but emerges for the first time in the primary visual cortex. Similarly, neuronal selectivity for stimulus velocity emerges in the middle temporal (MT) area which is anatomically at least two levels away from the primary visual cortex Maunsell and Newsome 1987;De Yoe and Van Essen, 1988;Livingstone and Hubel 1988), although the contributions of inputs other than the striate cortex and V2 to the stimulus selectivities of MT neurons make a simple serial hierarchy unlikely (Rodman et al 1989). …”
Section: Convergence Of Parallel Pathwaysmentioning
confidence: 99%
“…Girard et al (1991b) found that some neurons in V3a (dorsomedial area, DM) continued to respond to visual stimuli after the relevant portion of V1 was inactivated by cooling, and Rodman et al (1989) found that some neurons in MT retained responsiveness after lesions of V1 (for related results, see Girard et al, 1992). Because neurons in MT failed to respond to visual stimuli in monkeys with both V1 and superior colliculus (SC) lesions, a relay of visual information from the SC to the pulvinar and then to extrastriate cortex was postulated as the source of the visual activation of MT in the absence of V1 (Rodman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%